Understanding Discourse Competence in Translation - Masduki Masduki (IJEE (Indonesian Journal of English Education), 2015)
Discourse as a communication event is influenced by topic being communicated, interpersonal relationship between the communicants, and communication channel used in context. Whatever senses created by the communicants is fully related to culture and situation being involved. Participating in conversation, reading, writing, and translating, activates discourse competence, which requires the use of a set of strategy to realize or mobilize all declarative knowledge in the real context of communication. Further, this article highlights the discourse competence and how it is culturally implemented in translation as an activity of transferring messages. The discussion covers the overview of discourse competence, discourse approach, and discourse competence in translation.